EMBRYONIC POTENTIAL AND STEM CELLS - Agar, Nicholas (Bioethics, 2007)
This paper examines three arguments that use the concept of potential to identify embryos that are morally suitable for embryonic stem cell research (ESCR). According to the first argument, due to Ronald Green, the fact that they are scheduled for disposal makes embryos left over from IVF treatments morally appropriate for research. Paul McHugh argues that embryos created by somatic cell nuclear transfer differ from those that result directly from the meeting of sperm and egg in having potential especially conducive to the therapeutic use of their stem cells. I reject both of these arguments. According to the way of making distinctions in embryonic potential that I defend, it is the absence of a functional relationship with a womb that marks embryos morally suitable for ESCR.